(untitled) (Global Journal of Human-Social Science, 2012)
CBDRA is a tool to analyze the community involvement in disaster management programmes and strategies because the ultimate aim of any disaster management is for safer the community and also the local communities are always the first responder It helps to prepare people respond to disasters and recover from emergencies This paper deals with the concept of community based disaster management CBDM CBDRM explains different disasters and their impacts of disasters in Uttarakhand through disaster risk analysis and case studies For the data collection authors have used Participatory Rural Appraisal PRA tools interviews secondary data etc and for data analysis different techniques and software s like GPS Ilwis 3 7 Statistics and Arc 9 etc have been applied